Identification of Malassezia species from suspected Pityriasis (versicolor) patients. (Bangladesh Journal of Medical Microbiology, 2017)
Pityriasis versicolor is a chronic, superficial fungal infection affecting the superficial layer of a stratum corneum. Malassezia furfur is the major species involved in pityriasis versicolor. Currently many researchers reported increase in the incidence of other species as a causative agent of pityriasis versicolor. Isolation and identification of Malassezia species from suspected Pityriasis versicolor patients was conducted in the Department of Microbiology and immunology Bangabandhu Sheikh Mujib Medical University (BSMMU) from September 2013 to August 2014. Ninety two clinically diagnosed patients of Pityriasis versicolor were studied and samples from skin lesion were processed for direct microscopy and culture. Species of Malassezia were identified by cultural characteristics in Dixon's agar media by macro and microscopic observation of the colonies and by catalase test, urease test, esculin test and tween assimilation test. A totalof 92 cases 70(70.08%) were positive by direct microscopy and 50(54.34%) were positive by culture. Malassezia globosa was found in 38(76%) cases as the commonest etiological agent and Malassezia furfur was found in 10(20%) cases and Malassezia obtusa in 2 (4%) cases respectively.Bangladesh J Med Microbiol 2015; 9 (2): 17-19